Aeromedical retrieval diagnostic trends during a period of Coronavirus 2019 lockdown. Issue 12 (22nd December 2020) - Gardiner, Fergus W.; Gillam, Marianne; Churilov, Leonid; Sharma, Pritish; Steere, Mardi; Hannan, Michelle; Hooper, Andrew; Quinlan, Frank
Abstract: Background: Little is known on the trends of aeromedical retrieval (AR) during social isolation. Aim: To compare the pre, lockdown, and post‐lockdown AR patient characteristics during a period of Coronavirus 2019 (COVID‐19) social isolation. Methods: An observational study with retrospective data collection, consisting of AR between 26 January and 23 June 2020. Results: There were 16 981 AR consisting of 1983 (11.7%) primary evacuations and 14 998 (88.3%) inter‐hospital transfers, with a population median age of 52 years (interquartile range 29.0–69.0), with 49.0% ( n = 8283) of the cohort being male and 38.0% ( n = 6399) being female. There were six confirmed and 230 suspected cases of COVID‐19, with the majority of cases ( n = 134; 58.3%) in the social isolation period. As compared to pre‐restriction, the odds of retrieval for the restriction and post‐restriction period differed across time between the major diagnostic groups. This included, an increase in cardiovascular retrieval for both restriction and post‐restriction periods (odds ratio (OR) 1.12, 95% confidence interval (CI) 1.02–1.24 and OR 1.18 95%, CI 1.08–1.30 respectively), increases in neoplasm in the post restriction period (OR 1.31, 95% CI 1.04–1.64) and increases for congenital conditions in the restriction period (OR 2.56, 95% CI 1.39–4.71). Cardiovascular and congenital conditions had increased rates of priority 1 patients in the restriction and post restriction periods. There was a decrease in endocrine and metabolic disease retrievals in the restriction period (OR 0.72, 95% CI 0.53–0.98). There were lower odds during the post‐restriction period for retrievals of the respiratory system (OR 0.78, 95% CI 0.67–0.93), and disease of the skin (OR 0.78, 95% CI 0.6–1.0). Distribution between the 2019 and 2020 time periods differed ( P < 0.05), with the lockdown period resulting in a significant reduction in activity. Conclusion: The lockdown period resulted in increased AR rates of circulatory and congenital conditions.